Hjertets gudbilledlighed - Jensen, Erik Krebs (Grundtvig-studier, 1977)
The Heart as the Image of Godby Erik Krebs Jensen The image of God in the heart and the heart as the image of God are at one and the same time the divine and the truly human in man. Since the Creation the image of God has been hidden in the human heart, and in the course of history it will be illuminated more and more until at the end of history it will be completely revealed.The image of God is a riddle for man. By feeling and understanding, that is, receiving impressions of other images of God (in nature, in poetry or of Christ) the image of God in the heart can be illuminated. This meeting of images happens through the living interplay of the word between heart and heart. The word with God’s Spirit is an image of God - it is in fact Christ Himself in His resurrected form, speaking to man. This word must be heard audibly for it to make an impression on the heart so that the Spirit can touch it and move it. For the heart is created precisely in order to be open to spirit (both God’s and the Devil’s), and where the heart does not harden against it but is stirred by hearing God’s word, there the image of God in the heart’s core is revived, and this echoes in the mouth of man as a confession in a word of faith, hope or love. In this echo (an echo of God’s word) it is revealed to God and men and to man himself that he has adopted God’s word. Grundtvig puts it as strongly as this: God has reincarnated Himself. Every time a man hears God’s word, Jesus is reconceived, and He is reborn in the echoing word and thereby revealed to the world.This revelation of Christ in the word on the lips of men is an expression of God’s continuing creation and activity. God’s creative deed is always the same two-pronged action with one and the same result. At the Creation God made man out of clay and breathed His Spirit into him so that man could talk to God. In the fullness of time God made His power overshadow Mary and His Spirit descend upon Jesus, so that Jesus could talk to God on earth. (Jesus healed by touch and by speaking words). At baptism the sign of the cross is made and the child is baptized, thereby giving it the child’s right to pray, to confess and praise. Where God’s word touches the heart and the Spirit captivates the heart, and the heart responds with a “ Yes and Amen!” as an echo of what it has heard, there God’s creative presence in the word is experienced. And in the heart’s core the image of God is illuminated by the Spirit through the meeting between God’s image and its imprint.